Penerapan strategi pemasaran berbasis media digital pada usaha jasa logistik - Budiastuti, Ni Made; Kartikaningsih, Dewi; Yani, Ahmad; Mastaka , Ajoe Kartika (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
PT Trans Pratama Logistik is a company engaged in export, import, and domestic services. The purpose of this study is to analyze marketing strategies and digital media that influence the marketing process and analyze the benefits generated by marketing using digital media. In this study, the analysis and development of digital media-based marketing strategies for logistics services were carried out using the SWOT method. The research method used is a qualitative one, with data collection through interviews. The results of the SWOT analysis that has been carried out show that PT Trans Pratama Logistik, in terms of digital marketing, is in quadrant I. The strategy that is suitable for the company is an aggressive or growth-oriented marketing strategy. means the company must expand, enlarge, and accelerate the company's growth. One form of digital marketing that is suitable for application is the use of search engines, social media, and YouTube. PT Trans Pratama Logistik needs to strengthen company branding, develop products that function to maintain positioning, and improve service quality among competitors. In addition, the quality of the internet network needs to be improved in order to facilitate communication with potential customers. Invest in bandwidth usage and the network used.